Metode Dakwah Islam Wasatiyah KH Hasyim Asyari - Razi, Fahrur (Jurnal Komunikasi Islam, 2023)
This research endeavors to understand KH Hasyim Asyari's thoughts regarding wasatiyah da'wah. This study used a textual analysis method with a qualitative content analysis approach. In this regard, the heritage texts (turath) written by KH Hasyim Asyari and the text of a commentator (copyist) of Kiai Hasyim's ideas regarding wasatiyah preaching were inventoried, studied, then analyzed thematically. The results of this study illustrate that KH. Hasyim Asyari used the da'wah method bil-hikmah like when he was convincing Karl von Smith, the architect from Dutch, to convert to Islam. Additionally, he employed da'wah method bil-qalam through writing dozens of books, including those compiled in the title 'Irsyad Al Sari fi Jami Mushannafal al Syaikh Hasyim Asyari'. Further, in preaching wasatiyah, Kiai Hasyim argued that the difference of opinions among Muslims is not on the issue of usuluddin, but rather on furu' al-din, so that the differences with regard to schools of thought should not make Muslim society divided.